THE INFLUENCE OF THE KOREAN WAVE ON THE PURCHASE INTEREST OF SOUTH KOREAN CULINARY PRODUCTS WITH FOOD VLOGGERS AS A MODERATING VARIABLE - Lestyanto, Wahyu Budi; Andadari, Roos Kities (Jurnal Apresiasi Ekonomi, 2024)
Korean Wave is very popular in Indonesia so it is not surprising that it has many fans in Indonesia. The popularity of the Korean Wave has had an impact on the further development of South Korean culinary products. This is also supported by various reviews by several food vloggers which ultimately encourage consumer buying interest. This research aims to examine the influence of the Korean wave on interest in purchasing South Korean culinary products, and food vloggers as a moderating variable on the influence of the Korean wave on interest in purchasing South Korean culinary products. To obtain data, a sample of 100 respondents was taken representing Generation Y or millennials and Z in Salatiga City using the Purposive Sampling technique. The analytical tools used are simple regression analysis and Moderated Regression Analysis. The research results show that the Korean Wave has a positive effect on interest in buying South Korean culinary products. Apart from that, Food Vlogger strengthens the positive influence of the Korean Wave on interest in buying South Korean culinary products.